Wnt Signaling in Periodontal Disease - González-Quintanilla, David; Abásolo, Nicolás; Astudillo, Pablo (Frontiers in Dental Medicine, 2021)
Periodontitis is a multifactorial and chronic condition associated with the formation of a dysbiotic biofilm, leading to a pro-inflammatory environment that can modulate cell signaling. The Wnt pathway plays fundamental roles during homeostasis and disease, and emerging evidence suggests its involvement in the maintenance of the periodontium and the development of periodontitis. Here, we summarize the role of the Wnt/β-catenin and non-canonical Wnt signaling pathways in periodontitis. The accumulated data suggests specific roles for each branch of the Wnt pathway. Wnt5a emerges as a critical player promoting periodontal ligament remodeling and impairing regenerative responses modulated by the Wnt/β-catenin pathway, such as alveolar bone formation. Collectively, the evidence suggests that achieving a proper balance between the Wnt/β-catenin and non-canonical pathways, rather than their independent modulation, might contribute to controlling the progression and severity of the periodontal disease.